Calcium Homeostatic Pathways Change with Gestation in Human Myometrium1 - Tribe, R. M.; Moriarty, P.; Poston, L. (Biology of reproduction, 2000)
A rise in intracellular calcium is the primary trigger for contractile activity in pregnant human myometrium. It is hypothesized that key proteins involved in myometrial calcium homeostasis are gestationally regulated and play an important role in the preparation for labor. The aims of the study were to investigate the role of sarcoplasmic reticulum Ca ATPases (SERCAs) in regulating spontaneous contractile activity in myometrium, and to determine the expression of SERCA isoforms 2a and 2b, and the plasma membrane Ca ATPase (PMCA), at term and during labor. Western blot analysis demonstrated that the expression of SERCA 2a and 2b significantly increased in myometrium of women in labor compared with those not in labor. The augmentation of contractile activity in laboring myometrium in the presence of a SERCA 2 inhibitor, cyclopiazonic acid (CPA), demonstrated the functional significance of this observation. It is interesting that the application of CPA in the presence of a calcium-activated potassium channel inhibitor to term nonlabor myometrium mimicked the response of myometrium from women in active labor to CPA alone. We conclude that the activity of SERCA isoforms becomes increasingly important in the maintenance of regular contractile activity during labor and may compensate for the functional loss of other calcium control pathways at term.